Meningkatkan Motivasi Belajar Siswa melalui Implementasi Pendekatan Cognitive Behavior Therapy: Studi pada Siswa Kelas XII IPS SMA Muhammadiyah 1 Medan - Saharani, Della Putri; Kamilah, Amelia Afra; Lesmana, Gusman (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
Learning motivation is one important factor in achieving the educational goal, both in self and in the environment. Each student has a different motivation for following school studies. This article is written for the purpose of identifying and enhancing student learning motivation through the implementation of the cognitive behavior therapy approach. The research focuses on increased learning motivation, but certainly it also touches the image element. As for the methods used in this study by a descriptive qualitative approach that aims to describe phenomena, events and attitudes of a student group. The results of this study were obtained through data management, then analyzed and presented in the form of a chart pie, and the results of this study are students' learning motivations included in a medium-red category on the chart indicating the grade level of motivation for the students at the muhammadiyah 1 fields high school in the moderate category.